PSEUDOCHOLINESTERASE AS A PREDICTOR MARKER IN HYPOTHYROID PATIENTS - GG, Kaushik; Reena, Soni (International Journal of Clinical and Biomedical Research, 2018)
Introduction: Hypothyroidism is due to decreased circulating levels of Thyroid hormones and is caused by inadequate functioning of thyroid gland. Pseudocholinesterase (PCHE) is a nonspecific cholinesterase enzyme that hydrolyses choline based esters in plasma. The purpose of this study was to evaluate the serum level of PCHE in hypothyroid patients. Methodology: The present study was conducted on 100 newly diagnosed hypothyroid patients attending the Medical OPD. The results of patients were compared with 100 healthy controls of either sex of similar age group. Anthropometric measurements, T3, T4, TSH, PCHE & Cholesterol estimations were performed. Results: The mean serum PCHE (decrease) level was observed statistically highly significant (p<0.001) in hypothyroid patients as compared with healthy control subjects. A highly significant positive correlation between PCHE with T3 & T4 (p< 0.001) in hypothyroid cases. Conclusion: Serum Pseudocholinesterase may be helpful as biomarker in screening test for hypothyroidism along with thyroid stimulating hormone.